Effect of different surgical type of coronary artery bypass grafting on kidney injury: A propensity score analysis. Issue 45 (November 2017) - Chan, Ming-Jen; Lee, Cheng-Chia; Chen, Shao-Wei; Tsai, Feng-Chun; Lin, Pyng-Jing; Fan, Pei-Chun; Hsu, Hsiang-Hao; Chang, Ming-Yang; Chen, Yung-Chang; Chang, Chih-Hsiang
Abstract : Abstract: Acute kidney injury (AKI) after coronary artery bypass grafting (CABG) is associated with a less favorable outcome. Off-pump surgery results in lower kidney dysfunction than conventional on-pump arrest surgery. On-pump arrest surgery results in a lower revascularization rate compared with off-pump surgery. On-pump beating heart (OPBH) CABG combines the advantages of beating heart surgery and cardiopulmonary bypass. This study compared the renal outcomes of 3 cardiac surgical methods. From January 2010 to December 2012, 373 patients who underwent on-pump CABG were enrolled. Propensity analysis was performed to compare the postoperative outcomes of postoperative AKI, renal replacement therapy (RRT), intensive care unit (ICU) stay, mortality, and extubating time. In total, 98 patients received conventional on-pump surgery, 160 received OPBH surgery, and 115 received off-pump surgery. The Society of Thoracic Surgeons scores of these 3 groups were 6.1 ± 13.6, 7.4 ± 13.6, and 5.6 ± 10.9, respectively. Propensity analysis revealed lower AKI incidence in the off-pump group than in the on-pump surgery group. No substantial differences were observed in mortality, RRT, and the ICU stay between the off-pump and OPBH surgery groups. Among the 3 surgical methods, off-pump surgery results in lower AKI incidence. The short-term outcome, including kidney function, of OPBH surgery is similar to that of the off-pump group. Therefore, OPBH surgery is a considerable choice for patients with a high surgical risk. Abstract : Supplemental Digital Content is available in the text